Mediating effects of avatar realism on motivation in game based learning - review - Ahmad Zamzuri Mohamad Ali (Tanjong Malim, 2019)
Mediating effects of avatar realism on motivation in game based learning - review by Ahmad Zamzuri Mohamad Ali